Antagonistic activities of endophytic bacteria isolated from rice roots against the fungus Magnaporthe oryzae, a causal of rice blast disease - Quang Trung Do (Egyptian Journal of Biological Pest Control, 2022)
Abstract Background The blast disease of rice caused by the fungus Magnaphorthe oryzae is one of the most destructive diseases in Nam Dinh province, Vietnam. This study aimed to isolate and screen antagonistic bacteria isolated from the rice (Oryza sativa) against M. oryzae. Results In the present study, 14 endophytic bacteria were isolated from rice roots of a Ngoc Xuan variety in Nam Dinh province. The result showed that 6 isolates showed in vitro antagonistic activity against M. oryzae. Of 6, 2 strains, ND06 and ND10, molecularly identified as Bacillus velezensis and Pseudomonas putida, produced a significant inhibition on the pathogenic growth with growth inhibition of 62.87% and 64.25%, respectively, while the other 4 (ND03, ND07, ND09, and ND11) showed a weak inhibition. In addition, the ND06 and ND10 strains also presented antagonistic activity against M. oryzae under greenhouse conditions. Moreover, screening plant growth-promoting (PGP) traits of 2 isolates exhibited all 5 PGP traits including IAA production, phosphate solubilization, and production of ammonia, 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase, and siderophore. In addition, the greenhouse experimental results indicated that the cultivar rice seedlings inoculated with ND06 or ND10 strain produced a significant enhancement of the agronomic parameters (root length, shoot length, dry matter, and chlorophyll content). Conclusions The results indicated that the rice root endophytic bacteria (ND06 and ND10) possessed contemporarily multiple PGP traits and antifungal activity. These 2 strains should be further characterized in order to confirm the beneficial traits to develop as a potential biofertilizer and/or biocontrol agent for rice sustainable production.